Validity and reliability of the VRAG in a forensic psychiatric medium security population in Flanders. Issue 6 (2nd July 2016) - van Heesch, Ben; Jeandarme, Inge; Pouls, Claudia; Vervaeke, Geert
ABSTRACT: Since the development of the Violence Risk Appraisal Guide (VRAG), one of the most widely used actuarial risk assessment instruments, numerous replication studies have shown its usefulness in predicting (violent) recidivism among various offender populations. It is not clear, however, whether these findings can be generalized to forensic psychiatric patients admitted to a medium security forensic psychiatric unit in the Flemish part of Belgium. Therefore, the main aim of this study was to test the predictive validity and reliability of the VRAG in a sample of 191 Flemish medium security patients. The mean follow-up period was 2.4 years. Contrary to the expectations, the VRAG was unable to significantly predict any kind of outcome. Possible explanations are discussed and further research with the VRAG in Flanders, and its recently revised version, is recommended.